Pendampingan dalam Penerapan Arsitektur Ekologi pada Rumah Tinggal di Desa Sidoarum, Yogyakarta - Sari, Pawitra; Astuti, Retno Fitri; Putri, Isria Miharti Maherni; Fauziah, Femi (Maslahah: Jurnal Pengabdian Masyarakat, 2024)
The implementation of ecological architecture in residential homes to support healthy homes and habitable homes so that they can provide benefits for residents, health, the environment, and architecture. The method carried out is qualitative by mentoring to homeowners to understand about ecological architecture. The results of this mentoring are 1) the implementation of local wisdom through the use of local materials, namely red bricks and tiles and the use of yards, 2) human resource development through the skills of homeowners as builders, 3) utilization of knowledge by implementing ecological architecture, namely air, water, land/earth, and heat/fire, and 4) improvement of human health by implementing building orientation, circulation of windows and doors, and environmental control by managing the environment from damage such as air pollution and garbage.